Signed by Attilius - Jauch, Verena (Rei Cretariae Romanae Fautorum Acta, 2017)
In a 1997 article concerning Roman inscriptions on pottery from Eschenz, canton Thurgau, Switzerland, Bettina Hedinger and the author included the few pots signed by Attilius. For the research project ‘Limites inter provincias – Rome’s internal frontiers’ funded by Zurich’s cantonal archaeology department, the author examined and identified specific pottery types according to their typology, provenance and distribution in the Roman provinces of Raetia and Germania Superior. This research included the use of a portable XRFinstrument for clay body analysis. Since the appearance of the 1997 article more Attilius signed pots have been found: six examples from Zurich (cat. nos. 1, 2, 7, 9, 10, 14), one jar from Thurgau (cat. no. 8), and two new findings from Oberwinther and Eschenz (May 2016). The distinctive appearance of the signed ware by Attilius plus the discovery of new examples provided the impetus to revisit the subject within the framework of the provincial frontiers research project.